2000
DOI: 10.1074/jbc.m000621200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Apolipoprotein AI Gene Expression by Protein Kinase A and Kinase C through Transcription Factor, Sp1

Abstract: Our previous finding that insulin induces apolipoprotein AI (apoAI) transcription points to the participation of intracellular signaling. This finding prompted us to ask whether two classical G-protein-coupled signaling pathways requiring activated protein kinase A (PKA) or kinase C (PKC) may also regulate apoAI. Therefore, human hepatoma, Hep G2 cells stably transfected with pAI.474-CAT, a reporter construct spanning ؊474 to ؊7 of apoAI DNA fused to chloramphenicol acetyltransferase (CAT) were treated with 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 35 publications
4
50
1
Order By: Relevance
“…However, our results with PMA indicate that perturbation of PKC activity affects basal apoA 1 expression (Table 2). Similar results were recently demonstrated by Zheng et al (2000), who showed that PKC modulates apoA 1 promoter through the IRCE and the transcription factor SP1.…”
supporting
confidence: 76%
“…However, our results with PMA indicate that perturbation of PKC activity affects basal apoA 1 expression (Table 2). Similar results were recently demonstrated by Zheng et al (2000), who showed that PKC modulates apoA 1 promoter through the IRCE and the transcription factor SP1.…”
supporting
confidence: 76%
“…The stimulation of Sp1-mediated vascular permeability factor/ vascular endothelial growth factor transcription required an interaction between Sp1 and PKC (58). More recently, Sp1 was shown to be essential in the 12-O-tetradecanoylphorbol-13-acetate stimulation of human lysosomal acid lipase gene activity in monocytes (59) and in the regulation of apoAI gene expression by PKA and PKC (60).…”
Section: Discussionmentioning
confidence: 99%
“…However, insulin sensitization with thiazolidendiones may not always be sufficient to induce apo A-I expression (18,19). It appears that insulin acts on the apo A-I promoter through at least two signaling pathways: Ras-raf and phosphatidylinositol 3-kinase (PI3-K), leading to activation of the mitogen-activated protein kinase (MAPK) and PKC kinases, respectively (20). Despite these differences, all these pathways ultimately target the transcriptional factor Sp1 (20,21).…”
Section: Effect Of Glucose and Insulin On Apo A-i Gene Expressionmentioning
confidence: 99%
“…It appears that insulin acts on the apo A-I promoter through at least two signaling pathways: Ras-raf and phosphatidylinositol 3-kinase (PI3-K), leading to activation of the mitogen-activated protein kinase (MAPK) and PKC kinases, respectively (20). Despite these differences, all these pathways ultimately target the transcriptional factor Sp1 (20,21). Cotransfection of Sp1 expression vector with an apo A-I IRCE reporter construct augments the actions of insulin, while reducing Sp1 levels with an antisense RNA impairs the insulin response (17).…”
Section: Effect Of Glucose and Insulin On Apo A-i Gene Expressionmentioning
confidence: 99%